Hippo-YAP/TAZ-ROS signaling axis regulates metaflammation induced by SelenoM deficiency in high-fat diet-derived obesity - Jingzeng Cai; Jiaqiang Huang; Di Li; Xintong Zhang; Bendong Shi; Qiaohan Liu; Cheng Fang; Shiwen Xu; Ziwei Zhang (Journal of Advanced Research)
Introduction: Metabolic inflammation (metaflammation) in obesity is primarily initiated by proinflammatory macrophage infiltration into adipose tissue. SelenoM contributes to the modulation of antioxidative stress and inflammation in multiple pathological processes; however, its roles in metaflammation and the proinflammatory macrophage (M1)-like state in adipose tissue have not been determined. Objectives: We hypothesize that SelenoM could effectively regulate metaflammation via the Hippo-YAP/TAZ-ROS signaling axis in obesity derived from a high-fat diet. Methods: Morphological changes in adipose tissue were examined by hematoxylin-eosin (H&E) staining and fluorescence microscopy. The glucose tolerance test (GTT) and insulin tolerance test (ITT) were used to evaluate the impact of SelenoM deficiency on blood glucose levels. RNA-Seq analysis, LC-MS analysis, Mass spectrometry analysis and western blotting were performed to detect the levels of genes and proteins related to glycolipid metabolism in adipose tissue. Results: Herein, we evaluated the inflammatory features and metabolic microenvironment of mice with SelenoM-deficient adipose tissues by multi-omics analyses. The deletion of SelenoM resulted in glycolipid metabolic disturbances and insulin resistance, thereby accelerating weight gain, adiposity, and hyperglycemia. Mice lacking SelenoM in white adipocytes developed severe adipocyte hypertrophy via impaired lipolysis. SelenoM deficiency aggravated the generation of ROS by reducing equivalents (NADPH and glutathione) in adipocytes, thereby promoting inflammatory cytokine production and the M1-proinflammatory reaction, which was related to a change in nuclear factor kappa-B (NF-κB) levels in macrophages. Mechanistically, SelenoM deficiency promoted metaflammation via Hippo-YAP/TAZ-ROS-mediated transcriptional regulation by targeting large tumor suppressor 2 (LATS2). Moreover, supplementation with N-acetyl cysteine (NAC) to reduce excessive oxidative stress partially rescued adipocyte inflammatory responses and macrophage M1 activation. Conclusion: Our data indicate that SelenoM ameliorates metaflammation mainly via the Hippo-YAP/TAZ-ROS signaling axis in obesity. The identification of SelenoM as a key regulator of metaflammation presents opportunities for the development of novel therapeutic interventions targeting adipose tissue dysfunction in obesity.